A Cross-Country Comparison of National Nutrition Sufficiency Programs in ASEAN Member States: An Integrated Analysis of Strategies, Outcomes, and Best Practices - Putri, Nazwita Dewi (Rajaki of Tulip Medika Publisher, 2025)
The Association of Southeast Asian Nations (ASEAN) confronts a persistent